Smarthy window glass / Izah Liyanah Shahirudin and Hafizah Mohd Latiff - Shahirudin, Izah Liyanah; Mohd Latiff, Hafizah (2023)
Malaysia is known for its warm and humid climate, which can lead to challenges related to low thermal comfort for high-rise building occupants. The high temperatures and humidity levels are prevalent in many parts of the country which can result in discomfort glare and decline in people’s well-being who live and work in these conditions. In urban areas, the phenomenon is known as Urban Heat Island (UHI) effect exacerbates thermal discomfort. The overuse of artificial building materials, the lack of green spaces, and increased urbanisation contribute to higher temperatures in cities compared to their surrounding rural areas. As a result, residents often experience increased heat stress and discomfort, especially during hot seasons. In this study, the focus is to develop a smart and healthy window glass that can produce a thermal comfort temperature inside a building, as the window is one of the building elements that highly contributes towards the absorptivity of solar radiation. Furthermore, smart and healthy window glass can reduce the discomfort glare of building occupants.